Who watches the watchmen? Kelsen and Schmitt on the guardian of the Constitution - Felipe Alves da Silva (Cuestiones Constitucionales)
This article analyses one of the most well-known debates in 20th-century political and legal theory between Carl Schmitt and Hans Kelsen. Although it dates back to the early years of the Weimar Republic, the discussion of the guardian of the constitution focused on the years 1928 and 1931, when the personalistic character of power took place within discussions of constitutional jurisdiction. This article proposes to analyze part of Schmitt’s argument constructed during the 1920s that, to some extent, anticipates the arguments later developed in Der Hüter der Verfassung.